Available legal remedies to seek redress derived from the recent rulings by the European Court of Justice on tax matters: For the purpose of the recovery of the Spanish tax on retail sales of diesel and petrol, the so-called «céntimo sanitario» - Ibáñez García, Isaac (Revista de Contabilidad y Tributación. CEF, 2014)
Spanish Tax Authorities, for the purpose of the refund of the so-called «céntimo sanitario», consider and divulge that the only means (or procedure) for its administrative review is by way of the self-assessment tax return amendment. Now and then (and it seems to be clear as a result of ECJ Judgment in Case C-118/08 Transportes Urbanos y Servicios Generales, SAL of 26th January 2010) the affected tax payers have, among others, a direct action to request State-legislator’s liability. This alternative does not know the limits of final judgments, consent or statute of limitations of previous administrative acts, the effect of res iudicata, etc. Moreover, the affected taxpayer –who is such because of his/her reliance on a statutory rule which obliged him/her to bear this certain tax– does not have the obligation of filing the relevant action against a tax which has been awarded with presumption of legality. Therefore, on the occasion of the ECJ Judgment in Case C-82/12 Transportes Jordi Besora, SL of 27th February 2014, these issues are revived again and raise self-interested and false or interesting controversies.